Consumo de alimentos minimamente processados e ultraprocessados: um estudo em usuários de serviços de hemodiálise da Região Metropolitana da Grande Vitória-ES - Marques, Nina Mara Paterlini (2021)
Chronic Kidney Disease (CKD) has stood out among Chronic Noncommunicable Diseases (NCD) due to the significant increase in incidence and prevalence rates. Renal replacement therapy (RRT) becomes necessary in many cases, hemodialysis (HD) being the most common treatment. Although HD is effective in increasing survival rates, mortality among these patients is still high, and nutrition plays a key role in treatment. Therefore, we propose to evaluate the association of consumption of minimally processed and ultra-processed foods and socioeconomic factors, life habits and clinical characteristics of users of hemodialysis services in the Metropolitan Region of Grande Vitória (RMGV), Espírito Santo. For the purpose of this research, the foods were grouped according to the criteria of NOVA classification, according to the characteristics of the purpose and extent of industrial processing to which they were submitted. The results showed that users with less than 8 years of schooling (OR 1.706, 95%CI 1.125 - 2.589, p=0.012) and with income lower or equal to two minimum wages (OR 1.349, 95%CI 1.007 - 1.806, p=0.045) more likely to consume less minimally processed foods. Regarding ultra-processed foods, individuals aged 19 to 29 years had a higher chance of consuming them (OR 2.857, 95% CI 1.464 - 5.576, p=0.002). Analyzing occupation, users who were retired or on sick leave were 41.1% less likely to have higher consumption of processed foods (OR 0.589, 95%CI 0.432 - 0.804, p=0.001). Similarly, not engaging in work activity also reduced the chances of individuals consuming this group of food (OR 0.566, 95%CI 0.339 - 0.945, p=0.029). Those who did not practice physical activity were 36.2% less likely to consume ultra-processed foods (OR 0.638, 95%CI 0.459 - 0.888, p=0.008). Regarding smoking, being a current smoker increased by 2.3 times the risk of consuming ultra-processed foods (OR 2.349; 95%CI 1.237 - 4.462; p=0.009) in relation to those who did not smoke. Similarly, those who had the habit of consuming alcoholic beverages had 1.8 more risk of consuming these foods (OR 1.835; 95%CI 1.122 - 3.001; p=0.016). Finally, it was found that those patients with more than 6 years of treatment were almost 2 times more likely to consume ultra-processed foods (OR 1.975; 95%CI 1.227 - 3.180; p=0.005) compared to those with less time in treatment. It becomes necessary to evaluate food consumption through these food groups, as it allows to identify the vulnerability of the population to food excesses, and thus to adjust and propose intervention measures that ensure the health of HD service users.